Entry costs and stock market participation over the life cycle - Sule Alan (Institute for Fiscal Studies (IFS), 2005)
Several explanations for the observed limited stock market participation have been offered in the literature. One of the most promising one is the presence of market frictions mostly in the form of fixed entry and/or transaction costs. Empirical studies strongly point to a significant structural (state) dependence in the the stock market entry decision, which is consistent with costs of these types. However, the magnitude of these costs are not yet known. This paper focuses on fixed stock market entry costs. I set up a structural estimation procedure which involves solving and simulating a life cycle intertemporal portfolio choice model augmented with a fixed stock market entry cost. Important features of household portfolio data (from the PSID) are matched to their simulated counterparts. Utilizing a Simulated Minimum Distance estimator, I estimate the coefficient of relative risk aversion, the discount factor and the stock market entry cost. Given the equity premium and the calibrated income process, I estimate a one-time entry cost of approximately 2 percent of (annual) permanent income. My estimated model matches the zero median holding as well as the hump-shaped age-participation profile observed in the data.
Keywords: G11; D91; 330; Entry costs; Stock market; Structural estimation; Wertpapieranlage; Kleinaktionäre; Anlageverhalten; Markteintritt; Transaktionskosten; USA